Innovative Approaches to Addressing the Fundamental Materials Challenges in Hydrogen and Fuel Cell Technologies. Issue 46 (19th April 2016) - Miller, Eric L.; Randolph, Katie; Peterson, David; Rustagi, Neha; Cierpik-Gold, Kim; Klahr, Ben; Gomez, J Carlos
ABSTRACT: The emergence of hydrogen and fuel cell technologies in transportation and stationary power sectors offers the world important and potentially transformative environmental and energy security benefits. In recent years, research supported by the U.S. Department of Energy's (DOE) Fuel Cell Technologies Office has contributed substantially to the development of these technologies. Enhanced performance and reduced cost in automotive fuel cells are important examples of achievement. The research investments are clearly paying off, as commercial fuel-cell electric vehicles (FCEVs) are being rolled out by major car manufacturers today. With increasing market penetration of FCEVs, enabling technologies for the affordable and widespread production, storage and delivery of renewable hydrogen are becoming increasingly important. Long term commercial viability of hydrogen and fuel cells in the commercial marketplace will rely on continued materials research on several important fronts. Examples include the discovery and development of: (1) non-platinum-group-metal catalysts for next-generation fuel cells; (2) durable, high-performance photocatalytic materials systems for direct solar water splitting; (3) advanced materials-based systems for low-pressure, high-volumetric-density hydrogen storage; and (4) low-cost, hydrogen-compatible pipeline materials for hydrogen delivery and distribution. Research innovations in macro-, meso- and nano-scale materials are all needed for pushing forward the state-of-the-art in these areas. New approaches in accelerated materials development facilitated by a national Energy Materials Network of advanced scientific resources in theory, computation and experimentation are being adopted at DOE. Application of these approaches to address the key materials challenges in hydrogen and fuel cell technologies are discussed.